Effects of Green Human Resource Management on Employee Green Behavior: Moderating Role of Employee Environmental Knowledge - Karmoker, Kajol; Kona, Farhana Amin; Oyshi, Amanta Hasnat; Yasmin, Kazi Snigdha (International Journal of Sustainable Development & World Policy, 2021)
The study was conducted with an objective of measuring the effects of green human resource management (green HRM) practices on employee on-the-job and off-the-job green behavior within the context of garments industry in Bangladesh. Moreover, the study tested the moderating effects of employee environmental knowledge on the relationship between green HRM practices and employee on-the-job and off–the-job green behavior. A self-administered questionnaire survey was conducted in order to collect data from the participants. Two hundred and seventy employees working at the managerial level of garments factories in Bangladesh participated in the survey. Moderated regression analysis was employed to test the proposed research model. The study findings revealed that green HRM practices positively and significantly influenced employee on-the-job and off-the-job green behavior. This findings suggest that employee green behavior displayed both inside and outside the organization stem from the learnings and experiences inside the organization. Employee environmental knowledge was also found to moderate the effects of green HRM practices on employee on-the-job and off-the-job green behavior indicating that green HRM effects are stronger in case of environmentally concerned employees. The study findings provide HR professionals and policy makers with the guidance regarding the promotion of employee green behavior for improving environmental performance.